2021
DOI: 10.1186/s11556-021-00261-1
|View full text |Cite
|
Sign up to set email alerts
|

Change of physical activity parameters of hip and pelvic fracture patients during inpatient rehabilitation and after discharge: analysis of global and in-depth parameters

Abstract: Background A growing number of older adults suffer hip and pelvic fractures leading to hospital admission. They often result in reduced physical activity (PA) and impaired mobility. PA can be objectively measured with body-worn sensors. Usually, global cumulative PA parameters are analysed, such as walking duration, upright-time and number of steps. These traditional parameters mix different domains of PA, such as physical capacity (PC), behaviour and living environment. We examined the change … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 39 publications
0
4
0
Order By: Relevance
“…Therefore, additional parameters, such as variability or minimum and maximum performance, can be used for interpretation. Regarding gait analysis, such in-depth parameters have shown to be relevant for the interpretation of physical activity monitoring [ 30 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, additional parameters, such as variability or minimum and maximum performance, can be used for interpretation. Regarding gait analysis, such in-depth parameters have shown to be relevant for the interpretation of physical activity monitoring [ 30 ].…”
Section: Discussionmentioning
confidence: 99%
“…Although in a recent study PAV was able to discriminate between older healthy persons and stroke survivors [ 16 ], the construct of this measure remained unclear. According to the concept of the smallest worthwhile change, PAV measured by the activity monitor seems to be able to detect moderate effects (TEM < SWC0.6) [ 30 ]. The high association between PAV and peak power in our study demonstrates PAV as a surrogate parameter describing STS power.…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, STS ability has been associated with maximum gait speed [12], frailty and gait speed, and ADL and quality of life disability in females >60 years old [13]. Furthermore, Bagalà et al [14 used accelerometers to measure variations in acceleration during lie-to-sit-to-stand-to walk movements and reported their usefulness in assessing the quality of performance Zablotny et al [15] reported that observational analysis of sit-to-stand motion in older adults after hip fracture can be supported with quantitative data to evaluate intervention Other researchers used accelerometers to evaluate the time and speed of mobility [16] whereas some examined the amount of physical activity after fracture [17]. Although many studies have evaluated and examined movement qualities such as smoothness [5,7,14,18], to the best of our knowledge, none of the studies have used smoothness indices in STS motion.…”
Section: Participantsmentioning
confidence: 99%
“…Zablotny et al [15] reported that observational analysis of sit-to-stand motion in older adults after hip fracture can be supported with quantitative data to evaluate intervention. Other researchers used accelerometers to evaluate the time and speed of mobility [16], whereas some examined the amount of physical activity after fracture [17]. Although many studies have evaluated and examined movement qualities such as smoothness [5,7,14,18], to the best of our knowledge, none of the studies have used smoothness indices in STS motion.…”
Section: Introductionmentioning
confidence: 99%